Sistem Pakar Bimbingan Konseling Menerapkan Pola 17 Plus dengan Metode Forward chaining dan Certainty factor Berbasis Web - Fakrurrozi Fakrurrozi; Fauziah Fauziah; Andrianingsih Andrianingsih (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
A formal education institution is an institution that specifically aims to educate the younger generation before entering the world of work or lectures. With the existence of a school, it can provide smoothness in achieving optimal development for the younger generation, one of which is the existence of counseling services for the 17 plus pattern. This study aims to make it easier for teachers to approach students to identify students' interests and talents. Implementation of a website-based counseling application, from the problems that have been described, a system is needed that can facilitate teachers in handling student counseling. This expert system uses two methods, namely the forward chaining method to handle the facts of each question given by students and the certainty factor method used by the teacher to determine the treatment taken in consulting student interests and talents. System testing using the certainty factor method produces values from each field including personality field 49.67%, career field 67.94%, learning field 76.67%, and social field 71.67%.